2009
DOI: 10.1016/j.cellbi.2009.02.009
|View full text |Cite
|
Sign up to set email alerts
|

A GFP trap study uncovers the functions of Gilgamesh protein kinase in Drosophila melanogaster spermatogenesis

Abstract: The function of the gene gilgamesh (89B9-12) encoding a casein kinase in Drosophila spermatogenesis was studied. The chimeric Gilgamesh-GFP protein in spermatocytes is cortically located. In the polar and apolar spermatocytes, it concentrates at the terminal ends of the fusome, the organelle that passes through the system of ring canals of the spermatocyte cyst. At the stage of spermatid elongation, the protein associates with the nucleus. A spot of the highest Gilgamesh-GFP concentration in the nucleus co-loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…The molecular nature and features of these new PCP regulatory genes ranged from kinases, phosphatases, enzymes required for lipid biosynthesis or modification, to proteins involved in substrate degradation or modification. Among the kinases, CG7004 (four wheel drive/fwd) encodes a PI4kinaseß, which has been shown to be required for male germ-line development (Polevoy et al 2009), and CG6963 (gilgamesh/gish), a casein kinase1g, known to be involved in many processes including Wnt signaling (Davidson et al 2005), glial cell migration (Hummel et al 2002), and spermatogenesis (Nerusheva et al 2009). Phosphatases of the PAP2 family, CG11426 and CG11438, were also identified.…”
Section: Identification and Loss-of-function Analyses Of New Pcp Candmentioning
confidence: 99%
“…The molecular nature and features of these new PCP regulatory genes ranged from kinases, phosphatases, enzymes required for lipid biosynthesis or modification, to proteins involved in substrate degradation or modification. Among the kinases, CG7004 (four wheel drive/fwd) encodes a PI4kinaseß, which has been shown to be required for male germ-line development (Polevoy et al 2009), and CG6963 (gilgamesh/gish), a casein kinase1g, known to be involved in many processes including Wnt signaling (Davidson et al 2005), glial cell migration (Hummel et al 2002), and spermatogenesis (Nerusheva et al 2009). Phosphatases of the PAP2 family, CG11426 and CG11438, were also identified.…”
Section: Identification and Loss-of-function Analyses Of New Pcp Candmentioning
confidence: 99%
“…32 The microtubule cytoskeleton, as well as the actin cytoskeleton, seems to be important for individualization. Loss of the microtubule binding protein Abnormal Spindle (Asp) results in many spermatogenesis defects, including failed individualization.…”
mentioning
confidence: 99%
“…Previous study has reported that gish mutant germ cells contain abnormal actin cones in individualizing spermatid cysts 15 , this result implies that gish possibly affects the F-actin-mediated cell adhesion junctions. To explore whether the gish mutant GSCs lose adhesion to the hub, we visualized F-actin with phalloidin 15 and labeled GSCs with anti-Vasa antibody 17 .…”
Section: Resultsmentioning
confidence: 65%
“…We isolated a line with a P-element insertion in the third chromosome 15 , P{PZ} gish 04895 , which resulted in small testis and reduction in germ-cell number in homozygous mutant males. To thoroughly analyze the behavior of germ cells in gish 04895 mutant, we used anti-Fas III and anti-Vasa antibodies to visualize hub and germ cells 17, 18 , respectively (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation